Konsep Dasar Pembelajaran dalam Analisis Teori, Paradigma Baru, dan Praktik Pendidikan Efektif (Pusat Riset dan Inovasi Nasional, 2026)
This study examines the fundamental concepts of learning by emphasizing that learning is an active process that not only involves receiving information but also includes changes in students’ knowledge, attitudes, and skills. This research was conducted using a literature review method by exploring various relevant scholarly sources to understand the theories, principles, components, and factors that influence the success of learning. The findings indicate that learning theories such as behaviorism, cognitivism, constructivism, and humanistic theory provide an essential foundation for teachers in designing meaningful learning experiences. In addition, there has been a paradigm shift from teacher-centered learning to student-centered learning, which requires teachers to act as facilitators and designers of a conducive learning environment. The study further reveals that effective learning is determined by the alignment of objectives, materials, methods, media, learning activities, and evaluation. Internal factors such as students’ motivation and readiness to learn, as well as external factors such as teacher competence and the availability of learning facilities, also significantly influence learning outcomes. Overall, this study emphasizes that effective learning requires comprehensive planning, adaptive approaches, and classroom management that supports active student engagement.